Flexibility, performance and perceptions of job security: a comparison of East and West German employees in standard employment relationships - Janine Bernhardt; Alexandra Krause (Work, Employment and Society, 2014)
This article examines the determinants of perceived job security in German standard employment relationships (SER). Although SERs still dominate and shape the labour market, they have undergone several modifications in the recent past. Using survey data from 2006, the article examines how work organizations and particularly multiple workplace demands influence the perceived job security of employees in SERs. The article also asks whether - 20 years after reunification – structural and cultural differences still exist between East and West Germany. The results show that employees in East German SERs are more willing to accept flexibility and performance requirements. The article suggests that a new psychological contract has emerged, which promises long-term employment only if employees eventually meet the new workplace demands. Yet the overall lower job security of East Germans, fuelled by lower trust in their employers' information policies, indicates the fragile nature of this arrangement.
Keywords: 330; East Germany; flexibility; job security; performance requirements; standard employment relationships; West Germany